The Economics of Public Health Care Reform in Advanced and Emerging Economies - Coady, David (International Monetary Fund, 2012)
Using cross-country analysis and case studies, this book provides new insights and potential policy responses for the key fiscal policy challenges that both advanced and emerging economies will be facing.